Development and Validation of the AI Addiction Scale (AIAS-10): Measuring Compulsive and Emotional Dependence on AI Tools Among EFL Learners - Kasap , Süleyman; Babayiğit, Mehmet Veysi (Register Journal, 2026)
The current study developed and validated the AI Addiction Scale (AIAS-10) to measure problematic use of AI tools, such as ChatGPT. The purpose of the study was to address the lack of standardized instruments for assessing AI-related behavioral dependency in educational settings. Participants consisted of Muslim ELT/ELL students, reflecting the growing integration of AI tools in language learning contexts. Data from 267 users (students and professionals) were analysed to examine the psychometric properties of the scale. Factor analyses were conducted to identify its underlying structure, and reliability analyses were performed to assess internal consistency. The results showed that the scale reliably identifies two key dimensions of AI addiction: compulsive overuse and emotional dependence. The findings suggest that young adult learners in Muslim educational contexts may be more susceptible to over-reliance on AI for cognitive and language-related tasks. The AIAS-10 effectively captures unique AI-related issues, including over-reliance on cognitive tasks and anthropomorphizing AI systems. As AI becomes increasingly embedded in daily life, this validated tool provides researchers and clinicians with an important method for identifying unhealthy usage patterns. The findings highlight the need for educational guidelines and digital wellbeing strategies that promote balanced AI use in language learning, particularly within Muslim learner contexts.